A feasibility study on monitoring the evolution of apparent diffusion coefficient decrease during thermal ablation. Issue 9 (10th August 2015) - Plata, Juan C.; Holbrook, Andrew B.; Marx, Michael; Salgaonkar, Vasant; Jones, Peter; Pascal‐Tenorio, Aurea; Bouley, Donna; Diederich, Chris; Sommer, Graham; Pauly, Kim Butts
Abstract : Purpose: Evaluate whether a decrease in apparent diffusion coefficient (ADC), associated with loss of tissue viability (LOTV), can be observed during the course of thermal ablation of the prostate. Methods: Thermal ablation was performed in a healthy in vivo canine prostate model ( N = 2, ages: 5 yr healthy, mixed breed, weights: 13–14 kg) using a transurethral high‐intensity ultrasound catheter and was monitored using a strategy that interleaves diffusion weighted images and gradient‐echo images. The two sequences were used to measure ADC and changes in temperature during the treatment. Changes in temperature were used to compute expected changes in ADC. The difference between expected and measured ADC, ADCDIFF, was analyzed in regions ranging from moderate hyperthermia to heat fixation. A receiver operator characteristic (ROC) curve analysis was used to select a threshold of detection of LOTV. Time of threshold activation, t LOTV, was compared with time to reach CEM43 = 240, t DOSE . Results: The observed relationship between temperature and ADC in vivo (2.2%/ °C, 1.94%–2.47%/ °C 95% confidence interval) was not significantly different than the previously reported value of 2.4%/ °C in phantom. ADCDIFF changes after correction for temperature showed a mean decrease of 25% in ADC 60 min post‐treatment in regions where sufficient thermal dose (CEM43 > 240) was achieved. Following our ROC analysis, a threshold of 2.25% decrease in ADCDIFF for three consecutive time points was chosen as an indicator of LOTV. The ADCDIFF was found to decrease quickly (1–2 min) after reaching CEM43 = 240 in regions associated with heat fixation and more slowly (10–20 min) in regions that received slower heating. Conclusions: Simultaneous monitoring of ADC and temperature during treatment might allow for a more complete tissue viability assessment of ablative thermal treatments in the prostate. ADCDIFF decreases during the course of treatment may be interpreted as loss of tissue viability.